ANALYSIS OF VACCINATION COVERAGE AGAINST COVID-19 AND ADHERENCE AMONG OLDER ADULTS ANÁPOLIS, GOIÁS (CIPEEX, 2025)
Vaccination is an effective and cost-effective policy for preventing and controlling infectious diseases. In Brazil, vaccination coverage continues to grow, despite the challenges of an emerging country. However, several factors, such as poor adherence to campaigns, prevent such programs from being as effective as they should be. In this sense, it is necessary to help identify the barriers and challenges that prevent optimal adherence to vaccination. Given this, the present study aims to analyze COVID-19 vaccination coverage and adherence among adolescents in the municipality of Anápolis, Goiás. This is a cross-sectional, descriptive, and quantitative study developed using a semi-structured questionnaire that assessed vaccination coverage, adherence, and knowledge of the COVID-19 vaccine. Fifty adolescents were surveyed, of whom the majority were women (73.5%) aged between 12 and 17 years. Regarding the COVID-19 vaccine, 81.6% knew its function, but most did not know how it was made. Adherence to the first and second doses was high (87.8% and 79.6%), but only 41.7% completed the vaccination schedule with booster doses. Thus, the study showed high initial adherence to COVID-19 vaccination among adolescents in Anápolis, Goiás, with confidence in the vaccine's efficacy and safety. However, there was low adherence to booster doses, highlighting challenges such as fear of adverse effects and belief that it is not necessary.
Keywords: COVID-19 infections; Vaccination coverage; Knowledge